Pirate Radio in the Middle of the Forest - Marçall, Xan (Revista Vazantes, 2020)
It is a poetic-performative writing, with a strong autoethnographic characteristic, in which the life of a Kaabok transvestite from the Amazon is documented and poetic. A sensitive and aesthetic experience of life based on imagery references that are part of the Amazonian caboclo imaginary. It is a rhizomatic portrait of the Amazon and its constant disputes for material and immaterial independence.